The relative contributions of visual and semantic information in the neural representation of object categories. Issue 10 (27th September 2019) - Victoria, Lindsay W.; Pyles, John A.; Tarr, Michael J.
Abstract: Introduction: How do multiple sources of information interact to form mental representations of object categories? It is commonly held that object categories reflect the integration of perceptual features and semantic/knowledge‐based features. To explore the relative contributions of these two sources of information, we used functional magnetic resonance imaging (fMRI) to identify regions involved in the representation object categories with shared visual and/or semantic features. Methods: Participants ( N = 20) viewed a series of objects that varied in their degree of visual and semantic overlap in the MRI scanner. We used a blocked adaptation design to identify sensitivity to visual and semantic features in a priori visual processing regions and in a distributed network of object processing regions with an exploratory whole‐brain analysis. Results: Somewhat surprisingly, within higher‐order visual processing regions—specifically lateral occipital cortex (LOC)—we did not obtain any difference in neural adaptation for shared visual versus semantic category membership. More broadly, both visual and semantic information affected a distributed network of independently identified category‐selective regions. Adaptation was seen a whole‐brain network of processing regions in response to visual similarity and semantic similarity; specifically, the angular gyrus (AnG) adapted to visual similarity and the dorsomedial prefrontal cortex (DMPFC) adapted to both visual and semantic similarity. Conclusions: Our findings suggest that perceptual features help organize mental categories throughout the object processing hierarchy. Most notably, visual similarity also influenced adaptation in nonvisual brain regions (i.e., AnG and DMPFC). We conclude that category‐relevant visual features are maintained in higher‐order conceptual representations and visual information plays an important role in both the acquisition and neural representation of conceptual object categories.